2016
DOI: 10.1364/josaa.33.00a238
|View full text |Cite
|
Sign up to set email alerts
|

Metamer mismatching in practice versus theory

Abstract: Metamer mismatching (the phenomenon that two objects matching in color under one illuminant may not match under a different illuminant) potentially has important consequences for color perception. Logvinenko et al. [PLoS ONE10, e0135029 (2015)] show that in theory the extent of metamer mismatching can be very significant. This paper examines metamer mismatching in practice by computing the volumes of the empirical metamer mismatch bodies and comparing them to the volumes of the theoretical mismatch bodies. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…Lightness and chroma were positively correlated with the size of metamer mismatch areas [r(22) ¼ 0.53; p ¼ 0.008 and r(22) ¼ 0.57, p ¼ 0.004]. While the positive correlation with lightness is in line with previous observations, the positive correlation for chroma is not (Zhang et al, 2015(Zhang et al, , 2016. Lightness was also positively correlated to deviations from the natural target predictions [r(22) ¼ 0.56, p ¼ 0.004] in the color constancy task.…”
Section: Other Factorssupporting
confidence: 82%
See 2 more Smart Citations
“…Lightness and chroma were positively correlated with the size of metamer mismatch areas [r(22) ¼ 0.53; p ¼ 0.008 and r(22) ¼ 0.57, p ¼ 0.004]. While the positive correlation with lightness is in line with previous observations, the positive correlation for chroma is not (Zhang et al, 2015(Zhang et al, , 2016. Lightness was also positively correlated to deviations from the natural target predictions [r(22) ¼ 0.56, p ¼ 0.004] in the color constancy task.…”
Section: Other Factorssupporting
confidence: 82%
“…However, higher levels of metamerism may exist going from one natural scene to another, implying that metamer mismatching might be much higher than suggested by the above study (Foster et al, 2006). In fact, other studies observed that real surfaces show considerable degrees of metamerism and metamer mismatching (Logvinenko et al, 2015;Zhang et al, 2015Zhang et al, , 2016. Moreover, metamer mismatching is known to be an important problem in many practical contexts, such as printing (e.g., Fairchild & Johnson, 2004;Samadzadegan & Urban, 2013), lighting (e.g., Schanda, 2007;Viénot, Coron, & Lavédrine, 2011), photography (e.g., Belt, 2008, and art restoration (e.g., Berns, 2016).…”
Section: Uncertainty Of Surface Colorsmentioning
confidence: 61%
See 1 more Smart Citation
“…Both the optimal and practical spectral reflectance are used to analyze the degree of metamer mismatching for the digital imaging systems with different numbers of sensors; 25 303 486 practical spectral reflectance distributions were collected in a previous study, 13 and an additional 22 282 536 practical spectral reflectance distributions have been derived from 50 indoor and outdoor images captured under daylight, 27 indoor images F I G U R E 1 Spectral sensitivity functions of the digital imaging system with five (A) and seven (B) sensors captured under mixed artificial illumination, 32 and 201 images captured in natural outdoor lighting environments 33 by hyperspectral imaging systems. Overall, a database containing the spectral reflectance of 47 586 022 practical samples, from 400 nm to 700 nm at 10 nm intervals, was assembled.…”
Section: Spectral Reflectance Distributions Of Surface Colorsmentioning
confidence: 99%
“…The main purpose of constructing the discoloration model is to restore the fading 2 Journal of Spectroscopy artworks to their original colors in correct way. However, current discoloration models for red lead pigment are all based on the colorimetric theory, which were constructed in RGB or Lab color spaces and inevitably influenced by metameric problem [14].…”
Section: Introductionmentioning
confidence: 99%